2018
DOI: 10.2147/ijgm.s160741
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological factors and worldwide pattern of Middle East respiratory syndrome coronavirus from 2013 to 2016

Abstract: BackgroundMiddle East respiratory syndrome coronavirus (MERS-CoV) is an emerging threat to global health security with high intensity and lethality. This study was conducted to investigate epidemiological factors and patterns related to this disease.MethodsFull details of MERS-CoV cases available on the disease outbreak news section of the World Health Organization official website from January 2013 to November 2016 were retrieved; demographic and clinical information, global distribution status, potential con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…The available data indicates that in all age groups, male MERS cases had a higher SEYLL (10,702 years) in comparison to the female MERS cases (3817.5 years). Previous research has demonstrated a significant difference in mortality related to MERS between men and women [9,21].. In line with our finding, Maniecka-Bryla et al found that men diagnosed with the respiratory system disease in comparison to women had a higher SEYLL [22].…”
Section: Discussionsupporting
confidence: 91%
“…The available data indicates that in all age groups, male MERS cases had a higher SEYLL (10,702 years) in comparison to the female MERS cases (3817.5 years). Previous research has demonstrated a significant difference in mortality related to MERS between men and women [9,21].. In line with our finding, Maniecka-Bryla et al found that men diagnosed with the respiratory system disease in comparison to women had a higher SEYLL [22].…”
Section: Discussionsupporting
confidence: 91%
“…It has a high mortality rate, close to 35-40% of detected cases. 55 The natural reservoir of the virus is the dromedary camel, but most of the infections occur person to person, as it is highly transmissible. This can be verified in the outbreak that occurred in South Korea when one single patient transmitted the disease to 82 people when he went to the A&E. 56 Clinical description varies from asymptomatic cases to febrile symptoms with cough and respiratory distress, pneumonia and respiratory distress.…”
Section: Middle East Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…Es un coronavirus zoonótico que fue detectado por primera vez en 2012 en Arabia Saudí. Presenta una alta mortalidad, cercana al 35-40% de los casos detectados 55 . El reservorio natural del virus son los dromedarios, pero la mayor parte de los contagios se producen persona a persona, siendo altamente transmisible, como pudo comprobarse en el brote que ocurrió en Corea del Sur a raíz de un solo paciente que transmitió la enfermedad a 82 personas al acudir al servicio de urgencias 56 .…”
Section: Síndrome Respiratorio De Oriente Medio Por Coronavirusunclassified